Who detects corporate fraud under the thriving of the new media? Evidence from Chinese‐listed firms. (28th February 2020) - Sun, Yanmei; Sun, Xiaoting; Wu, Weixing
Abstract: We test the effectiveness of corporate fraud‐detection mechanisms and the reaction of the capital market to the information released by the various types of detectors. Using corporate fraud data from 2006 to 2015, we find that the media is the most important external market system used to expose corporate fraud to the public. However, in contrast to the low incidents of fraudulent firms being exposed by analysts and short sellers, firms with abnormal short selling are more likely to be revealed to the public. Furthermore, the market reacts significantly negatively to the frauds exposed by the media.